Optimal design of rotary compressor oriented to end-plate gas injection with check valve. (April 2018) - Wang, Baolong; Liu, Xingru; Ding, Yunchen; Shi, Wenxing
Highlights: General expressions of the envelopes and areas of the injection regions are developed Effects of eccentricity and piston thickness on the injection region area are investigated Injection region area reaches the maximum when piston thickness is two times of eccentricity. Abstract: The gas injection technology had been developed to enhance the performance of the single cylinder rotary compressor at high compression ratio. However, the improvement of current designs was unsatisfactory because of the limited effective mass injected. A novel end-plate injection structure with check valve for rotary compressor was proposed and its advantages were confirmed in a previous study. In order to enlarge the injection port, increase the gas injected, and eventually increase performance enhancement, the general expressions of the envelopes and areas of the injection regions are developed based on an analytical geometry method in this paper. Based on them, the effects of the design parameters, such as the eccentricity and the thickness of the rolling piston, on the injection region area are investigated. Finally, an optimal design method for the rotary compressor oriented to proposed end-plate gas injection with check valve is raised. As a conclusion, for an arbitrary rotary compressor with designated cylinder radius, the area of the injection region reaches the maximum when the thickness of the rolling piston is equal to two times of the eccentricity.